Developing a Tonsawang Vocabulary Application for Elementary School Students - Langi, Vicky Rolando; Tuturoong , Nancy Jeane; Matius Lumenta , Arie Salmon (Devotion : Journal of Research and Community Service, 2026)
Tonsawang is one of the regional languages in North Sulawesi that is increasingly less frequently used by younger generations, raising concerns regarding its preservation. The lack of interactive and accessible learning media for elementary school students remains a challenge in introducing Tonsawang vocabulary effectively. This research aimed to design and develop a mobile-based Tonsawang vocabulary learning application for elementary school students. The application was developed using the Rapid Application Development (RAD) method, which includes the requirements planning, user design, construction, and cutover stages. The application was implemented using Android Studio and the Kotlin programming language and was evaluated using Black Box testing and the System Usability Scale (SUS). The results showed that all application functions operated successfully, achieving a 100% success rate. Field testing also demonstrated that the application effectively supported independent learning and received positive responses from students, as indicated by high usability scores. Therefore, the application can serve as an effective digital learning medium while supporting the preservation of the Tonsawang language in the modern era.